Uporaba virtualnih očal pri pouku biologije v devetem razredu osnovne šole - Šarman, Darja (Revija inovativna pedagogika, 2025)
The article presents a case study on the use of virtual reality (VR) glasses in Grade 9 biology lessons in primary school. The theoretical part introduces the concept of virtual reality and describes the preparation and implementation of lessons using VR glasses. The study aims to determine whether VR glasses enhance pupils' understanding of the subject matter and encourage their motivation. The research aims to analyze pupils' work to assess their comprehension and conduct a survey to gain insight into their experiences, motivation for using VR glasses, acquired knowledge, and opinions on the usefulness of VR technology in lessons compared to text-based resources. Based on the results, we conclude that VR technology can be an effective educational tool, especially when used thoughtfully and in combination with other teaching methods. Additionally, pupils develop digital competencies, mainly information and data literacy. Despite the positive effects, challenges remain, such as technical limitations and the teacher's preparation for this lesson format.
Keywords: biologija; biology; digital competencies; digital technology; digitalna tehnologija; digitalne kompetence; osnovne šole; primary schools; virtual reality glasses; virtualna očala